Assembly of polysubstituted chiral cyclopropylamines via highly enantioselective Cu-catalyzed three-component cyclopropene alkenylamination. Issue 81 (15th September 2020) - Zhang, Yu; Li, Yuan; Zhou, Wei; Zhang, Mengru; Zhang, Qian; Jia, Ran; Zhao, Jinbo
Abstract : A Cu-based chiral catalyst enables convergent, highly enantioselective three-component assembly of alkenyl cyclopropylamines containing up to all three stereogenic centers. Abstract : Enabled by a commercial bisphosphine ligand, the Cu-catalyzed three-component cyclopropene alkenylamination with alkenyl organoboron reagent and hyroxyamine esters proceeds with exceptionally high enantioselectivity to deliver poly-substituted cis -1, 2-alkenylcyclopropylamines that contain up to all three stereogenic centers on the cyclopropane.